Dampak Magang Merdeka Belajar Kampus Merdeka Bagi Mahasiswa Akuntansi - Lidia Memori Hia; Samuel Oktavianus; Shania Katherine Sidebang; Tan Ming Kuang (Owner : Riset dan Jurnal Akuntansi, 2023)
An internship is an integral part of the higher education curriculum to broaden students' practical understanding of the real world. This research focuses on the Magang Merdeka Belajar Kampus Merdeka (MBKM) program, which was introduced by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia in early 2020. The program aims to facilitate students' gaining real-world experience through relevant work practices in their field of study, thereby enhancing graduates' hard and soft skills. Therefore, this research aims to identify the skills acquired by accounting students during their participation in MBKM internship activities across various industries. This study utilized a survey method by distributing a Google Form through social media to accounting students throughout Indonesia who participated in the MBKM internship. The valid sample size obtained was 90 out of 105 eligible respondents, and the data was analyzed using descriptive statistical approaches. The analysis results indicate that the majority of surveyed students have made progress in both hard and soft skills required in the workplace. The majority of students agree that their internship has helped them enhance their confidence in working in the field of accounting and their abilities to work independently and solve problems autonomously, collaborate with others, present in front of the public, analyze data, and exercise judgment in task completion. This study also found that the internship program is effective in enhancing the skills required by the business and industry sectors, resulting in the majority of internship participants receiving job offers upon graduation